Reflex seizures in rare monogenic epilepsies. (April 2022) - Krygier, Magdalena; Zawadzka, Marta; Sawicka, Agnieszka; Mazurkiewicz-Bełdzińska, Maria
Abstract: Reflex seizures (RSs) are epileptic events consistently induced by specific triggers. They occur in epilepsies of varied etiologies and are often accompanied by spontaneous seizures. The genetic background of RSs is heterogeneous and polygenic or multifactorial inheritance is suspected in the majority of cases. Although causative single-gene variants are rarely identified, the number of genes associated with RSs is gradually increasing. In this article, we describe individuals presenting reflex seizures as predominant epileptic events in whom we identified pathogenic and likely pathogenic variants in CACNA1A, GNAO1, and NOVA2 genes. In addition, we summarize rare monogenic epilepsies associated with RSs. The presence of RSs in our patients expands the phenotypic spectrum of the diseases and contributes to our knowledge of the underlying monogenic defects in reflex seizures.